An Experimental and Computational Study of Zeolitic Imidazole Framework (ZIF-8) Synthesis Modulated with Sodium Chloride and Its Interaction with CO2 - Lita Priandani; Amarilis Aliefa; Oka Pradipta Arjasa; Fajar Inggit Pambudi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The increase of CO2 level in atmosphere becomes one of the driving forces for research on functional materials. Capturing and utilizing of CO2 are more important than ever, both to reduce CO2 emission and to increase the economic value of CO2 derivatives. In this study, synthesis of metal-organic frameworks (MOFs) was conducted by combining Zn2+ metal nodes and 2-methylimidazolate ligand to form zeolitic imidazolate frameworks (ZIF-8) materials. ZIF-8 was synthesised with the addition of sodium chloride to modulate the crystal morphology during the in-situ synthesis, using either water or methanol as the solvent. According to the refinement of the X-ray diffraction pattern, the ZIF-8 materials were successfully prepared and have unit cell parameters that are reasonably close to the available standard. The formation of ZIF-8 is also confirmed by IR spectroscopy, which reveals the stretching vibration mode of Zn−N from the coordination between Zn2+ and 2-methylimidazolate ligand. The crystal morphology exhibits different shape, as observed in SEM and TEM studies, with the dominant shape being a rhombic dodecahedron. The interaction between ZIF-8 and CO2 was investigated via ex-situ IR spectroscopy, combined with several computational techniques such as density functional theory and molecular dynamics, to elucidate the nature of the CO2 binding sites. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).